1999
DOI: 10.1088/0031-9155/44/12/304
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of low-angle x-ray scattering from some biological samples

Abstract: Design of medical imaging devices based on the detection of low-angle coherent scattering is a subject of increasing interest. The technique is based on the differences in the distribution of photons coherently scattered from different body tissues. Coherent scattering is also useful in monitoring changes that may occur in a healthy tissue (e.g. carcinoma). In this work, low angle scattering properties of some tissues and tissue-equivalent materials are studied. Special care is given to the possibility of dist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 29 publications
0
13
0
1
Order By: Relevance
“…where we have used the transition amplitude (6). Here the integration over the impact parameter b yields immediately the δ function δ(k ⊥1 − k ′ ⊥1 ).…”
Section: E Scattering On a Macroscopic Atomic Targetmentioning
confidence: 99%
See 1 more Smart Citation
“…where we have used the transition amplitude (6). Here the integration over the impact parameter b yields immediately the δ function δ(k ⊥1 − k ′ ⊥1 ).…”
Section: E Scattering On a Macroscopic Atomic Targetmentioning
confidence: 99%
“…From a theoretical viewpoint, the Rayleigh scattering has attracted much interest as one of the simplest second-order quantum electrodynamical (QED) process [4]. From a practical viewpoint, detailed knowledge of the properties of elastically scattered photons has been found important for applications in material research [5], medical imaging [6], and astrophysics [7].…”
Section: Introductionmentioning
confidence: 99%
“…Johns and Wismayer (2004) reported that a degree of variation existed in the form factor values obtained using different diffractometers. Elshemey et al (1999) used a Monte Carlo simulation code employing measured molecular form factors by Peplow and verghese (1998) in order to examine the possibility of tissue characterization of several biological samples.…”
mentioning
confidence: 99%
“…In this work, a Monte Carlo simulation code is modified so that it becomes capable of simulating x-ray scattering from mixed two-component samples. The code is compared with the old version (Elshemey et al 1999) for x-ray scattering from single-component samples. It is also compared with practical measurements for single and mixed biological samples with predefined components percentages by volume.…”
mentioning
confidence: 99%
“…[1][2][3][4] O crescente interesse em tais medidas deve-se à natureza característica do espalhamento coerente da radiação. Dessa forma, LAXS de amostras biológi-cas, como o sangue e seus componentes, têm importância nos campos da biologia e medicina.…”
Section: Introductionunclassified